Association between diabetes and mortality in elderly patients admitted for a first episode of acute heart failure. Issue 4 (28th November 2017) - Formiga, Francesc; Chivite, David; Montero, Abelardo; Petit, Irene; Moreno‐González, Rafael; Franco, Jonathan; Corbella, Xavier
Abstract : Aim: To examine whether the presence of a prior diagnosis of diabetes mellitus (DM) influences mortality risk in elderly patients experiencing a first episode of heart failure (HF) hospitalization. Methods: A total of 677 consecutive patients aged ≥75 years admitted for a first episode of acute decompensated heart failure were evaluated according to the presence or not of DM, and in‐hospital and 1‐year mortality rates were evaluated. Results: A total of 240 patients (35.4%) had a diagnosis of DM. Overall, 42 patients (6.2%) died during admission; and 205 patients (30.3%) died after 1 year; however, no differences were observed in mortality rates between both groups. Cox univariate analysis did not identify prior DM diagnosis as a risk factor for 1‐year mortality (HR 0.767, P < 0.082). Multivariate analysis identified older age (HR 1.101, P < 0.0001), lower preadmission Barthel Index (HR 0.987, P = 0.002), higher heart rate (HR 1.013, P = 0.02), higher admission serum potassium (HR 1.471, P = 0.016) and non‐prescription of angiotensin‐converting enzyme inhibitors or angiotensin II receptor antagonists (HR 1.597, P = 0.018) as independent risk factors for 1‐year mortality. Conclusions: More than one‐third of elderly patients experiencing a first admission because of acute heart failure decompensation had a prior diagnosis of DM. However, DM did not seem to be associated to a significant 1‐year mortality risk.Geriatr Gerontol Int 2018; 18: 554–560 .